Stress-resistant corals may not acclimatize to ocean warming but maintain heat tolerance under cooler temperatures - Verena Schoepf (Nature Portfolio, 2019)
Coral populations from thermally extreme conditions may help restore reefs degraded by bleaching. Here, the authors show that these corals can maintain their heat tolerance despite acclimation to colder temperatures but have a limited capacity to acclimatize to ocean warming.